Effectiveness of Online Learning and Preparedness of Preschool Teachers Amid COVID-19 Pandemic - Danielle Apos Ocaya, Isabelle (International Research in Education, 2024)
Education is a significant factor in success. It is seen as a hope to have a bright future. Today, education has evolved through the use of technology. Technology helps to enhance learning, increase engagement, and improve teaching techniques. This study aims to determine the effectiveness of preschool online learning during the COVID-19 pandemic in the identified schools in Lapu-Lapu City for the school year 2020 -2021. This study used a descriptive correlational research design and survey technique with 35 teacher respondents. A survey questionnaire was designed to assess the perception of teachers on the effectiveness of online learning for young learners. Frequency count, percentage, and weighted mean were used to treat the data gathered. The level of effectiveness of preschool online learning was measured in four aspects: online learning platform used, learning materials used, techniques and methods used, and engagement of students in class. The level of preparedness was also calculated based on criteria. A test subjected to a 0.05 level of significance was used to know if there was a significant relationship between the responses and the demographic profile of the respondents. The results of this study revealed that the respondents found online learning to be moderately effective. They are also only somewhat prepared for online teaching. Furthermore, the study revealed that there is no significant relationship between the teachers’ perception of the level of effectiveness and preparedness and their demographic profile. Based on the findings, an action plan was formulated and recommended for implementation by the authorities concerned.